2015
DOI: 10.17509/ijal.v5i1.824
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Communicative Attitudes Among Japanese Efl Pupils

Abstract: This paper describes how gender and age affect Japanese pupils' motivation for learning English and their attitudes to communication with people from different cultures. A new foreign language curriculum was introduced to Japanese elementary schools in 2011. Although each school can officially choose any foreign language in its own right, most elementary schools are now conducting English activity. However, as most homeroom teachers lack both experiences and qualifications for teaching English, this activity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…Many studies found that female students combine the two types of motivation instrumental and integrative for learning English compare to their counterpart males which seems to have instrumental motivation to accomplish their personal purposes such as getting a job (Akram & Ghani, 2013). Adachi's (2015) study indicated that female students are motivated as a result of their attitudes towards English whereas, males are motivated by the people surrounding them. As a result of the gap between female students and male students' motivation in language learning, this article highlights this relation according to social and cultural factors in the Arab world compared to non-Arab world.…”
Section: Gender Variance In Learning English Motivationmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies found that female students combine the two types of motivation instrumental and integrative for learning English compare to their counterpart males which seems to have instrumental motivation to accomplish their personal purposes such as getting a job (Akram & Ghani, 2013). Adachi's (2015) study indicated that female students are motivated as a result of their attitudes towards English whereas, males are motivated by the people surrounding them. As a result of the gap between female students and male students' motivation in language learning, this article highlights this relation according to social and cultural factors in the Arab world compared to non-Arab world.…”
Section: Gender Variance In Learning English Motivationmentioning
confidence: 99%
“…Adachi's (2015) study revealed that male students' motivation for learning English was influenced by their parents. According to Azarnoosh and Birjandi (2012), in Iran, particularly male students bring honor to their family when they speak English proficiently.…”
Section: Motivation and Social Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it is difficult to determine whether participant rejection of the cooperative approach reflected opinions formed as a result of these classroom experiences, or whether they are rooted in cultural attitudes shared amongst a wider learner community. It is possible that the absence of English communication in the day-to-day life of most Japanese people, and its perceived status in Japan as a foreign language, rather than an L2 (Adachi, 2015;Amburgey, 2015;Maftoon & Ziafar, 2013), could help explain this collective response by participants.…”
Section: Qualitative Data Analysismentioning
confidence: 99%